ONLINE LENDING: BETWEEN MASLAHAH AND MAFSADAH - Abd. Haris; Nurfaika (BAMALA Institute, 2025)
This study examines the phenomenon of online lending (Pinjol) that has become increasingly prevalent in recent times, characterized by its ease and speed in serving people who need money through rapid lending processes. Various needs of lower and middle-class communities are diverse, ranging from business requirements, entrepreneurial ventures, to urgent needs that cannot be avoided at certain times. The need of borrowers (creditors) to obtain loans from lenders (debtors) is certainly driven by necessity, and religion tolerates assisting those in need, as stated in the Qur'an. Creditors offer various forms of quick and easy facilities without difficulty, which appears to be beneficial (maslahah) for debtors. However, the benefits offered by lenders (debtors) through online platforms are not entirely within the context of maslahah. Various harms (mafsadah) and gaps in society have been found, such as reports of fraud (gharar), threats, and other issues experienced by victims who borrow (creditors). This research employs library research methodology, which is a series of efforts or activities that explore data collection through literature related to this study. This work draws from the Qur'an, tafsir (Qur'anic exegesis), books, articles, and relevant websites related to this theme. Therefore, this study examines the appropriate principles when observing the reality occurring in society, particularly in online lending (Pinjol). Based on various real elements, online lending does not fully guarantee maslahah within it; analyzing maslahah and mafsadah aspects is crucial as a reference in lending and borrowing practices. The concern is that the dangers and threats far outweigh the comfort, pleasure, and happiness without threats. The theoretical framework employed is Al-Taraki's theory (b. 1917 CE - d. 1979 CE), which explains that maslahah is a characteristic found in legal arrangements for mukallaf (legally responsible individuals) in the form of drawing benefits and rejecting all forms of harm. Additionally, this study analyzes Qur'anic verse al-Baqarah/2: 245 as a form of reward or recompense from Allah, comparing lenders (debtors) who create difficulties experienced by borrowers (creditors).